A sustained-release antibacterial silver-based fiber and preparation method thereof
Through the method of wrapping silver with nanofibers, sustained-release antibacterial silver-based fibers are prepared, which solves the problems of poor binding of silver with fibers and environmental pollution in the prior art, and achieves efficient and environmentally friendly antibacterial effects.
Patent Information
- Application Number
- CN202311258430.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-09-27
AI Technical Summary
In the existing preparation methods of silver-based fibers, silver or silver ions are poorly combined with the fiber main material, resulting in a decrease in antibacterial activity, and the silver-loading method has problems of environmental pollution and high waste.
Silver-loaded nanofibers are prepared by wrapping silver or silver ions by nanofibers, and added them to the spinning stock solution. The sustained-release antibacterial silver-based fibers are prepared by wet spinning technology.
The close combination of silver and fiber is achieved, the utilization rate of silver is improved, the production process is reduced, the peeling of silver and the toxicity of high concentration silver are avoided, and the long-term antibacterial effect is also achieved.
Smart Images

Figure CN117306010B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silver-based fibers, and in particular relates to a slow-release antibacterial silver-based fiber and a preparation method thereof. Background Art
[0002] As a functional fiber, silver-based fiber has advantages such as higher comfort, better antibacterial and excellent radiation resistance, and has broad application prospects in the fields of biomedicine, electronics, optical catalysis, textile industry, etc. The industrial preparation technology of silver-based fiber needs to be improved, and the commercial application and promotion market of silver-based antibacterial fiber is huge.
[0003] At present, there are two main methods for preparing silver-based fibers. One is the pre-silver loading technology, that is, silver element and silver ions are compounded with the fibers during molding or semi-molding to prepare functional silver-based fibers. This method has the main problems of poor combination of silver or silver ions with the main fiber material or change in the form of loaded silver during later fiber processing, thereby reducing the antibacterial activity of silver or silver ions; the other is to load silver on the surface of the fiber after molding, which is generally divided into physical and chemical methods for fiber treatment. The chemical silver loading method will have a certain impact on the environment and generally there will be residual impurity ions, which makes it difficult to meet the high medical standards. Although the physical method is environmentally friendly and has a higher purity, for sputtering-plated fibers, the waste rate of target materials is relatively high.
[0004] In view of the advantages and disadvantages of silver loading before and after, it is necessary to improve the silver loading method or the silver adding method so that the silver can be closely combined with the main fiber material and reduce the impact of the later treatment on the silver. We process the silver loading into a sustained release state by wrapping silver or silver ions in nanofibers, and the selected nanofibers have a good degree of combination with the main fiber, thus forming a sustained release antibacterial silver-based fiber that integrates silver and fiber. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a slow-release antibacterial silver-based fiber;
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned slow-release antibacterial silver-based fiber;
[0007] The sustained-release antibacterial silver-based fiber uses nanofibers as a carrier of silver to make silver-loaded nanofiber slurry. The silver-loaded nanofiber slurry is added to the spinning solution of polyacrylonitrile (PAN) or polyvinyl acetal (Vinalon), and the sustained-release antibacterial silver-based fiber is prepared through a wet spinning machine. The sustained-release and antibacterial properties of the fiber are tested and analyzed, and the results show that it has sustained-release antibacterial properties.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a sustained-release antibacterial silver-based fiber comprises the following steps:
[0010] Step 1: Preparation of silver-loaded nanofibers: dissolving nanocellulose in pure water to obtain a nanocellulose solution with a mass concentration of 5%; grinding the nanocellulose solution with an ultrafine pulper, adding silver slurry to make the molar ratio of silver to nanocellulose 0.5-1.1, and then grinding the solution finely and centrifuging to obtain a lower precipitate which is the silver-loaded nanofibers;
[0011] Step 2: preparing silver-based fiber spinning solution, selecting one of polyacrylonitrile or polyvinyl acetal as the main fiber material and preparing the main fiber spinning solution, keeping the main fiber spinning solution at 105°C-115°C and maintaining a constant temperature; adding the silver-loaded nanofiber prepared in step 1 to the main fiber spinning solution, wherein the silver in the silver-loaded nanofiber accounts for 0.1%-5% of the main fiber material, and mixing them evenly to form the silver-based fiber spinning solution;
[0012] Step 3: Preparation of silver-based fibers: using wet spinning technology on the silver-based fiber spinning solution to obtain rolled silver-based fibers through spinning, coagulation, drawing, cleaning, and winding.
[0013] Preferably, the fiber diameter of the nanocellulose is ≤100 nm.
[0014] Preferably, in step 1, the nanocellulose solution is roughly ground with an ultrafine refiner at a speed of 1500 rpm for 30 minutes.
[0015] Preferably, the size of the micro-nano silver particles in the silver paste is between 0.1 μm and 1 μm.
[0016] Preferably, in step 1, the nanocellulose solution with silver paste added is finely ground with an ultrafine grinder at a rotation speed of 2500 rpm for 30-60 min.
[0017] A sustained-release antibacterial silver-based fiber is prepared by the above-mentioned preparation method of the sustained-release antibacterial silver-based fiber.
[0018] The preparation principle of the present invention is as follows:
[0019] Since the nanofibers in nanocellulose have multiple functional groups and the surface effect of nanomaterials, the surface particles lack the coordination of adjacent atoms, so the surface energy is increased and extremely unstable, and it is easy to combine with other atoms, showing strong activity, so the nanofibers form a certain bonding effect with silver, thereby fixing the silver particles. The silver-loaded nanofibers and the main spinning solution obtained by coarse and fine grinding are both polymer structures, have certain compatibility, and can be polymerized with the main fiber material.
[0020] In the present invention, the nanofibers in the nanocellulose act as silver carriers, allowing the nanofibers to load silver and evenly disperse it into the main fiber spinning solution, so that the nanofibers and silver are evenly loaded on the main fiber. In addition, since nanocellulose has a certain wrapping property for silver, the antibacterial property of the prepared silver-based fiber is a process of slowly releasing from the outside to the inside, which can have a long-lasting antibacterial effect.
[0021] In the present invention, the main functions of coarse grinding are grinding + mixing, wherein uniform mixing is the main purpose; the slurry obtained by fine grinding is a homogeneous and stable suspension, which can be left for 24-48 hours without obvious stratification.
[0022] During the preparation of the silver-based fiber spinning solution, the main fiber spinning solution is kept at 105°C-115°C and kept at a constant temperature, preferably 110°C. If the temperature is too high, the main fiber will decompose, and if the temperature is too low, the viscosity of the main fiber spinning solution will be too high.
[0023] In the present invention, the silver paste can be a mixture of micro-nano structured silver particles (micro-nano structured silver particles are referred to as micro-nano silver or micro-nano silver particles, which refer to structured particles of micron to nanometer scale, and are products with micron properties and nanometer properties. Micro-nano structured particles are not easily directly absorbed by the human body and have high safety performance) and water, wherein the micro-nano silver particles used in the present invention have a size of 0.1 μm to 1 μm. A single substance slurry of a substance such as silver nitrate, silver chloride, micro-nano silver, or a mixture slurry of multiple substances can also be selected. In the present invention, micro-nano silver is preferred in the silver paste because it has the advantages of stable properties, broad-spectrum bactericidal, long-lasting antibacterial, non-toxic and non-irritating.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. High utilization rate of silver. Compared with the late silver-loading technology of the wire, especially the chemical silver plating technology, which causes serious waste of precious metals, in the present invention, the loss of silver is less during the preparation process of the silver-loaded nanofibers, which improves the utilization rate of silver and makes full use of precious metals;
[0026] 2. Silver loading is directly carried out during the fiber forming process to reduce the production process;
[0027] 3. Micro-nano silver can be directly loaded into the wire, and the silver and the main material of the wire are firmly combined, effectively avoiding the occurrence of silver shedding;
[0028] 4. Micro-nano silver is loaded into the thread, and the release of micro-nano silver is slow and trace, which can not only play a long-term sustained-release antibacterial effect but also avoid the toxicity of high concentration of silver to cells.
[0029] 5. The present invention uses nanocellulose and micro-nano silver to disperse micro-nano silver through the nano effect to obtain silver-loaded nanofibers, which is a physical reaction. Compared with the prior art of loading silver on fibers through chemical reactions such as oxidation-reduction, it avoids the problems of chemical reagent residues and low silver content after oxidation-reduction reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope photograph of Example 6 of the present invention.
[0031] Figure 2 This is the full energy spectrum of Example 6 of the present invention.
[0032] Figure 3 This is the C, O, and Ag energy spectrum diagram of Example 6 of the present invention.
[0033] Figure 4 This is the element spectrum of Example 6 of the present invention.
[0034] Figure 5 Graph showing the relationship between Ag release and time for Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0035] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.
[0036] Nanocellulose is a natural organic polymer material with a highly ordered structure and a diameter less than 100nm. It has abundant oxygen-containing functional groups on its surface and can be easily chemically modified or modified to prepare cellulose derivatives for the synthesis of functional polymer materials.
[0037] In the specific implementation process, the main fiber spinning stock solution in step 2 is prepared by selecting one of polyacrylonitrile or polyvinyl acetal as the main fiber material, that is, polyacrylonitrile (PAN) or polyvinyl alcohol (PVA) is added with a small amount of additives in a dissolving kettle at a certain temperature to form a solution. Its preparation process and required substances are existing technologies and will not be repeated here.
[0038] After the silver-based fiber is prepared, the silver-based fiber can be tested. The prepared silver-based fiber is tested for Ag sustained release and antibacterial properties. A certain amount of silver-based fiber is placed in pure water, and samples are taken every other day. The silver content in the water is tested by inductively coupled plasma emission spectroscopy (ICP) to evaluate the Ag release of the silver-based fiber in the water. + According to the national standard GB / T20944.3-2008 oscillation method, the concentration of live bacteria in the silver-based fiber was tested after oscillating for 18 hours to detect its antibacterial rate. The national standard requires an antibacterial rate of ≥70% to be qualified.
[0039] The following examples are used to verify the technical effects of the present invention, and comparative experiments are carried out to optimize production parameters. Example 1
[0040] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper and coarsely ground at a speed of 1500rpm for 30min, and then 0.67g of silver paste with a solid content of 75% (equivalent to 0.5g of silver mass) was added, and finely ground at a speed of 2500rpm for 30min. The slurry obtained by grinding was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers. Polyacrylonitrile (PAN) was selected as the main fiber material of the fabric, and the prepared main fiber spinning solution was kept warm to 105℃ and kept at a constant temperature; the prepared silver-loaded nanofiber was added to the main fiber spinning solution according to the percentage of silver in the main fiber mass of 0.1%, and the mixture was evenly mixed to form a silver-based fiber spinning solution. The silver-based fiber spinning solution was wet-spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0041] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 74%. Example 2
[0042] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper for coarse grinding at a speed of 1500rpm for 30min, and then 1.5g of silver paste with a solid content of 75% (equivalent to 1.1g of silver mass) was added, and fine grinding was carried out at a speed of 2500rpm for 60min. The grinding slurry was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers. Polyacrylonitrile (PAN) was selected as the main fiber material of the fabric, and the prepared main material spinning solution was kept warm to 110° and kept at a constant temperature; the prepared silver-loaded nanofiber was added to the main material fiber spinning solution in an amount of 2% of the mass percentage of silver in the main material fiber, and the mixture was evenly mixed to form a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0043] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 90%. Example 3
[0044] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper for coarse grinding at a speed of 1500rpm for 30min, and then 1.5g of silver paste with a solid content of 75% (equivalent to 1.1g of silver mass) was added and finely ground at a speed of 2500rpm for 60min. The slurry obtained by grinding was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers for standby use. Polyvinyl alcohol (PVA) was selected as the main fiber material of the fabric, and the prepared main material spinning solution was kept warm to 110° and kept at a constant temperature; the prepared silver-loaded nanofibers were added to the main material fiber spinning solution in an amount of 5% of the mass percentage of silver in the main material fiber, and the mixture was evenly mixed to form a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0045] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 98%. Example 4
[0046] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper and coarsely ground at a speed of 1500rpm for 30min, and then 1g of silver paste with a solid content of 75% (equivalent to 0.75g of silver mass) was added and finely ground at a speed of 2500rpm for 60min. The slurry obtained by grinding was separated by a high-speed centrifuge, and the lower layer of sediment was recovered as silver-loaded nanofibers for standby use. Polyvinyl alcohol (PVA) was selected as the main fiber material of the fabric, and the main material spinning solution was kept warm to 110° and kept at a constant temperature; the prepared silver-loaded nanofibers were added to the main material fiber spinning solution in an amount of 3% of the weight percentage of silver in the main material fiber, and the silver-based fiber spinning solution was uniformly mixed to obtain a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0047] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 92%. Example 5
[0048] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper and coarsely ground at a speed of 1500rpm for 30min, and then 0.8g of silver paste with a solid content of 75% (equivalent to 0.6g of silver mass) was added and finely ground at a speed of 2500rpm for 40min. The slurry obtained by grinding was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers for standby use. Polyacrylonitrile (PAN) was selected as the main fiber material of the fabric, and the main material spinning solution was kept warm to 110° and kept at a constant temperature; the prepared silver-loaded nanofibers were added to the main material fiber spinning solution in an amount of 4% of the main material fiber mass percentage, and the silver-based fiber spinning solution was mixed evenly to obtain a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0049] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 91%. Example 6
[0050] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper for coarse grinding at a speed of 1500rpm for 30min, and then 1.5g of silver paste with a solid content of 75% (equivalent to 1.1g of silver mass) was added, and fine grinding was performed at a speed of 2500rpm for 50min. The grinding slurry was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers for standby use. Polyvinyl alcohol (PVA) was selected as the main fiber material of the fabric, and the main material spinning solution was kept warm to 115° and kept at a constant temperature; the prepared silver-loaded nanofibers were added to the main material fiber spinning solution at a silver mass percentage of 5% of the main material fiber, and the silver-based fiber spinning solution was mixed evenly to obtain a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0051] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 98%. Various test results are shown in the attached figure.
[0052] Comparative Example 1
[0053] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper for coarse grinding at a speed of 1500rpm for 30min, and then 1.5g of silver paste with a solid content of 75% (equivalent to 1.1g of silver mass) was added, and fine grinding was carried out at a speed of 2500rpm for 60min. The grinding slurry was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers for standby use. Polyvinyl alcohol (PVA) was selected as the main fiber material of the fabric, and the main material spinning solution was kept warm to 110° and kept at a constant temperature; the prepared silver-loaded nanofibers were added to the main material fiber spinning solution in an amount of 2% of the mass percentage of silver in the main material fiber, and the silver-based fiber spinning solution was uniformly mixed to obtain a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0054] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 92%.
[0055] Comparative Example 2
[0056] 5g of nanocellulose and 95g of pure water were mixed to obtain a nanocellulose solution, which was put into an ultrafine pulper and coarsely ground at a speed of 1500rpm for 30min, and then 1.5g of silver paste with a solid content of 75% (equivalent to 1.1g of silver mass) was added and finely ground at a speed of 2500rpm for 60min. The slurry obtained by grinding was separated by a high-speed centrifuge, and the lower sediment was recovered as silver-loaded nanofibers for standby use. Polyacrylonitrile (PAN) was selected as the main fiber material of the fabric, and the main material spinning solution was kept warm to 110° and kept at a constant temperature; the prepared silver-loaded nanofibers were added to the main material fiber spinning solution in an amount of 5% of the mass percentage of silver in the main material fiber, and the silver-based fiber spinning solution was uniformly mixed to obtain a silver-based fiber spinning solution. The silver-based fiber spinning solution was subjected to wet spinning technology, and the silver-based fiber spinning solution was subjected to spinning-solidification-drawing-cleaning-winding to obtain a finished silver-based fiber roll.
[0057] Take 0.5g of the prepared silver fiber, add 50mL of pure water, and take samples every day under the condition of constant temperature water bath shaking at 25℃. Use atomic absorption spectrophotometer to measure the Ag content in the solution to test the relationship between Ag release and time. According to the national standard GB / T20944.3-2008 oscillation method, the silver-based fiber was shaken for 18 hours and then the live bacteria concentration was tested. The antibacterial rate was 98%.
[0058] See also Figure 1 As shown, this is an electron scanning microscope photograph of Example 6, from which it can be seen that the prepared silver fiber has good formability and uniformity.
[0059] See also Figure 2 As shown, it is the full spectrum of Example 6, from which it can be seen that the Ag element and the C and O elements as the main material elements are evenly distributed, indicating that Ag is evenly distributed in the prepared fiber.
[0060] See also Figure 3 As shown, it is the C, O, and Ag spectrum diagram of Example 6. It can be seen that the element distribution in the single element spectrum and the full spectrum diagram is consistent, indicating that Ag is uniformly distributed in the prepared fiber.
[0061] See also Figure 4 As shown, it is the element spectrum and content of Example 6. It can be seen that the corresponding elements can be detected by electron scanning microscopy combined with spectrum analysis, and the Ag weight percentage is 5.18%. Since this detection method cannot detect the H element in the main fiber material, the Ag content is too high when the content is displayed, so it can be basically determined that the Ag content is consistent with the theoretical content of 5%.
[0062] See also Figure 5 As shown, it is a graph showing the relationship between Ag release and time of Examples 1-6. It can be seen that by oscillating the silver fiber in water and taking water samples every day for Ag content testing, the Ag content in the water gradually increased, and increased slowly after 15 days. The Ag content basically tended to be stable after about 30 days, indicating that the Ag release in the silver fiber has a sustained sustained release.
[0063] The above specific implementation methods and examples are specific support for the technical idea of applying a sustained-release antibacterial silver-based fiber and its preparation method and application proposed by the present invention, and cannot be used to limit the protection scope of the present invention. Any equivalent changes or equivalent modifications made on the basis of this technical solution in accordance with the technical idea proposed by the present invention still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a sustained-release antibacterial silver-based fiber, characterized in that: The following steps are involved: Step 1: Preparation of silver-loaded nanofibers: dissolving nanocellulose in pure water to obtain a nanocellulose solution with a mass concentration of 5%; After the nanocellulose solution is coarsely ground with an ultrafine pulper, silver slurry is added to make the molar ratio of silver to nanocellulose be 0.5-1.1, and then finely ground and centrifuged to obtain the lower precipitate which is the silver-loaded nanofiber; Step 2: preparing silver-based fiber spinning stock solution, selecting one of polyacrylonitrile or polyvinyl acetal as the main fiber material and preparing the main fiber spinning stock solution, keeping the main fiber spinning stock solution at 105°C-115°C and maintaining a constant temperature; adding the silver-loaded nanofiber prepared in step 1 to the main fiber spinning stock solution, wherein the silver in the silver-loaded nanofiber accounts for 2%-5% of the main fiber material, and mixing them evenly to form the silver-based fiber spinning stock solution; Step 3: Preparation of silver-based fibers: using wet spinning technology on the silver-based fiber spinning solution to obtain rolled silver-based fibers through spinning, coagulation, drawing, cleaning, and winding; The silver paste is a mixture of micro-nano silver particles and water, and the size of the micro-nano silver particles in the silver paste is 0.1 μm-1 μm.
2. The method for preparing a sustained-release antibacterial silver-based fiber according to claim 1, characterized in that: The fiber diameter of the nanocellulose is ≤100 nm.
3. The method for preparing a sustained-release antibacterial silver-based fiber according to claim 1, characterized in that: In the step 1, the nanocellulose solution is coarsely ground with an ultrafine pulper at a rotation speed of 1500 rpm for 30 minutes.
4. The method for preparing a sustained-release antibacterial silver-based fiber according to claim 1, characterized in that: In the step 1, the nanocellulose solution with silver paste added is finely ground with an ultrafine grinder at a rotation speed of 2500 rpm for 30-60 minutes.
5. A sustained-release antibacterial silver-based fiber, characterized in that: The invention discloses a slow-release antibacterial silver-based fiber prepared by the method for preparing the slow-release antibacterial silver-based fiber according to any one of claims 1 to 4.
Citation Information
Patent Citations
Slow-release antibacterial polyacrylonitrile fibers and preparing method and application thereof
CN109778336A
Preparation method of silver and nitrogen doped cellulose-based carbon aerogel film for fuel cell
CN116387582A